The Mog-1 Gene Is Required for the Switch from Spermatogenesis to Oogenesis in Caenorhabditis Elegans - Graham, P. L. (1993)
Caenorhabditis elegans hermaphrodites make first sperm, then oocytes. By contrast, animals homozygous for any of six loss-of-function mutations in the gene mog-1 (for masculinization of the germ line) make sperm continuously and do not switch into oogenesis. Therefore, in mog-1 mutants, germ cells that normally would become oocytes are transformed into sperm. By contrast, somatic sexual fates are normal, suggesting that mog-1 plays a germ line-specific role in sex determination. Analyses of double mutants suggest that mog-1 negatively regulates the fem genes and/or fog-1: mog-1; fem and mog-1; fog-1 double mutants all make oocytes rather than sperm. Therefore, we propose that wild-type mog-1 is required in the hermaphrodite germ line for regulation of the switch from spermatogenesis to oogenesis rather than for specification of oogenesis per se. In addition to its role in germ-line sex determination, maternal mog-1 is required for embryogenesis: most progeny of a mog-1; fem or mog-1; fog-1 mother die as embryos. How might the roles of mog-1 in the sperm/oocyte switch and embryogenesis be linked? Previous work showed that fem-3 is regulated post-transcriptionally to achieve the sperm/oocyte switch. We speculate that mog-1 may function in the post-transcriptional regulation of numerous germ-line RNAs, including fem-3. A loss of mog-1 might inappropriately activate fem-3 and thereby abolish the sperm/oocyte switch; its loss might also lead to misregulation of maternal RNAs and thus embryonic death.